RANTAI NILAI BERAS IR64 DI KECAMATAN WANAREJA KABUPATEN CILACAP - Mahfud Hidayat; Pujiharto Pujiharto; Sulistyani Budiningsih (Universitas Muhammadiyah Purwokerto, 2017)
This research aimed to describe the supply chain of IR64 Rice Variety, to analyze the supply chain management of IR64 Rice Variety, and to analyze the value chain of the rice variety in Wanareja Sub-District of Cilacap Regency. The research method used was survey with non-random Purposive Sampling technique. The number of respondents were 15 farmers, 5 retailers, 5 merchant collectors and 5 wholesalers of IR64 rice variety. The research was conducted for six months, starting from July 2017 until January 2018.The results showed that the commerce agents of IR64 rice variety trading in Wanareja sub-district were farmers, merchant collectors, wholesalers and retailers. The chamber of commerce is divided into three types: the first channels, the second channels and the third channels. The function of supply chain of IR64 rice variety included role of the trading agents like IR64 rice variety farmers who run a role as merchantmen in the process of producing and selling IR64 rice variety. Meanwhile merchant collectors, wholesalers and retailers run their roles in storaging, purchasing and selling the rice variety. The farmer's marketing efficiency was 18% and the added value was IDR 10.486.100, for one harvest season. While the merchant collector's marketing efficiency was 95.56%, marketing margin was IDR 24 per kg of rice and distribution of marketing margin was 97.42%. The wholesalers' marketing efficiency was 94.54%, marketing margin was IDR 120, - per kg of rice and distribution of marketing margin is 98.70%. The retailer's marketing efficiency is 94.92%, marketing margin IDR 420, - per kg of rice and 95.78% marketing margin distribution. The value added of merchant collectors, wholesalers and retailers were IDR 1.402.000, -; IDR 4.840.400, - and IDR 938.000, -. The analysis of value chain of IR64 rice variety in Wanareja Sub-district of Cilacap Regency showed that value of marketing efficiency, marketing margin, marketing distribution and value added obtained by farmers, merchant collectors, wholesalers and retailers were efficient and profitable.